Oxyfuel Combustion in a Bubbling Fluidized Bed Combustor. (January 2016) - Hrdlicka, Jan; Skopec, Pavel; Opatril, Jan; Dlouhy, Tomas
Abstract: This paper deals with characterization of the oxyfuel combustion in a bubbling fluidized bed. The paper proposes a calculation procedure to evaluate gas flow streams, adiabatic flame temperature and concentrations of species in the flue gas. The second part describes a laboratory scale 30 kW oxyfuel BFB and presents results of experiments with various semi-oxyfuel and full oxyfuel modes. The results are compared with experimental results, the agreement is satisfactory with less than 10% relative difference. Sustaining of similar fluidization regime along all different cases resulted in decrease of the adiabatic flame temperature that had to be compensated by thermal volumetric load increase from 3.3 to 4.1 MW/m 3 .